The governance of the financial action task force: an analysis of power and influence throughout the years. - de Oliveira, Inês Sofia (Crime, Law & Social Change, 2018)
The international fight against money laundering illustrates changes in global governance as a result of the increasingly cross-border nature of crime and the need it creates for all involved to cooperate. The economic priorities and security concerns that surround it contributed to the strong evolution of global governance in this area and the status of anti-money laundering as a shared problem. The creation of the Financial Action Task Force (FATF), its expansion and cementation throughout the years, is a good example of the many forces working together to responding to the demands of emerging criminal threats and trends. It offers a good illustration of how relationships in global governance have influenced FATF’s priorities and action and ultimately the way in which illicit financial flows are tackled. This analysis offers an overview of FATF’s network across time taking into account the role of states, international organisations, and the private sector in the decision-making processes. It argues that Great Powers - a small, but aligned, group of states of global economic relevance - are responsible for FATF’s direction and the international efforts against illicit financial flows. It suggests, however, that unlike what could be expected, their power is declining following the rise of private sector influence through resourceful, organised and transnational actions e.g. on information sharing.